Fish ecology - Wootton, R.J. (Chapman & Hall, 1992)
This is intended as an introduction for advanced undergraduates and postgraduates in marine ecology, freshwater ecology, fish biology, fisheries ecology and aquaculture. It adopts a habitat-based approach, ranging from head waters to ocean depths, and from tropics to polar regions, thereby loosely reflecting the organization of general ecology textbooks and demonstrating how the principles of contemporary ecology can be applied to fishes.